Executive Processes Underpin the Bilingual Advantage on Phonemic Fluency: Evidence From Analyses of Switching and Clustering - Marsh, John E.; Hansson, Patrik; Sörman, Daniel Eriksson; Ljungberg, Jessica Körning (Frontiers in Psychology, 2019)
Bilinguals often show a disadvantage in lexical access on verbal fluency tasks wherein the criteria require the production of words from semantic categories. However, the pattern is more heterogeneous for letter (phonemic) fluency wherein the task is to produce words beginning with a given letter. Here, bilinguals often outperform monolinguals. One explanation for this is that phonemic fluency, as compared with semantic fluency, is more greatly underpinned by executive processes and that bilinguals exhibit better performance on phonemic fluency due to better executive functions. In this study, we re-analyzed phonemic fluency data from the Betula study, scoring outputs according to two measures that purportedly reflect executive processes: clustering and switching. Consistent with the notion that bilinguals have superior executive processes and that these can be used to offset a bilingual disadvantage in verbal fluency, bilinguals (35–65 years at baseline) demonstrated greater switching and clustering throughout the 15-year study period.